Pengaruh Metode Bermain Peran Terhadap Keberanian engungkapkan Bahasa Pada Anak Kelompok B Di Tk Pertiwi Kahuman I Polanharjo KlatenTahun Ajaran 2016/2017 - Saputri, Citra Bunga Mustika Dullah; , Sri Slamet S,Pd., M.Pd (2017)
The research on group B TK Pertiwi Kahuman I was motivated by the courage of children in expressing the diverse guages. There was a child who was shy when speaking and answering questions from the teacher. Child's interaction is still lacking of to other chidren and the courage of children was still passive. The purpose of this study was to determine the effect of a method of role playing for the courage express language on the children in group B at TK Pertiwi Kahuman I Polanharjo Klaten Academic Year 2016/2017. The research was design experiment research with one group pretest-posttest. The subject in this study was all student of group B at TK Pertiwi Kahuman I, 16 children. The method of data collection was observation, documentation, interview and test. Technique of data analysis used t-test analysis. The results data indicated that t calculate ≤ table-t 24.706 ≤ -1.753 furthurmore Ho was rejected and Ha was aceepted. It can be inferred that there is the influence of role play method to encourage the express language in the children the group B at Tk Pertiwi Kahuman I Polanharjo Klaten Academic Year 2016/2017.Keyword: Role Play Method, and The Encourage of Language Express